Pengaruh Disiplin Kerja, Motivasi dan Lingkungan Kerja terhadap Kinerja Guru Pondok Pesantren Dar Al-Raudhah Pangkalanbun Kalimantan Tengah - Djafar ravensky; Muhammad Bukhori; Tin Agutina Karnawati (STKIP PGRI SITUBONDO, 2023)
This research was conducted at the Dar Al-Raudhah Islamic Boarding School. This study aims to determine and analyze 1) the effect of work discipline on the performance of dar al-raudhah Islamic boarding school teachers 2) the effect of motivation on the performance of dar al-raudhah Islamic boarding school teachers 3) the effect of the work environment on the performance of dar al-raudhah Islamic boarding school teachers 4) the influence of work discipline, motivation and work environment on the performance of Dar Al-Raudhah Islamic boarding school teachers. The population of this study were all teachers who were the 44 samples for the study. Data were taken from a field survey using a questionnaire with a sampling method using saturated sampling. This study uses a quantitative approach with the data to be analyzed must meet the validity and reliability tests, and also test the classical assumptions first, namely the normality test, heteroscedasticity test, and multicollinearity test. The data analysis used is multiple linear regression. The results of this study partially show 1) work discipline has an effect on the performance of Dar Al-Raudhah Islamic Boarding School teachers, 2) motivation has an effect on the performance of Dar Al-Raudhah Islamic Boarding School teachers 3) work environment has no effect on the performance of Dar Al-Raudhah Islamic Boarding School teachers. The results simultaneously show that 4) work discipline, motivation and work environment affect the performance of Dar Al-Raudhah Islamic Boarding School teachers